First report of Phytophthora gonapodyides causing root rot on raspberry in Canada - Burlakoti, Rishi Ram (Plant disease, 2023)
Raspberry (Rubus idaeus L.) is an economically important fruit crop in Canada and about 80% of red raspberries are cultivated in British Columbia. In 2018, foliar symptoms associated with root rot and wilting complex disease were observed in raspberry field of Fraser Valley areas of British Columbia. Plants were stunted with reduced numbers of primocanes. Chlorosis and necrosis on leaves and partial wilting of branches were observed. When plants were uprooted, necrosis and browning on roots were observed. Two isolates of oomycetes pathogen were isolated using baiting with rhododendron leaves and pear fruit as described in Sapkota et al. 2022. Using FastDNA Spin kit (MP Biomedical, Burlingame, CA), genomic DNA of pathogen isolates was extracted from mycelia cultured on 20% clarified V8 agar medium amended with 10 mg pimaricin, 250 mg ampicillin, 10 mg rifampicin (V8PAR) per liter following the manufacturer's standard protocol. Pathogens were identified using colony morphology on 20% clarified V8 PAR as well as internal transcribed spacer (ITS) sequencing with ITS1 primers (White et al. 1990) and multiplex targeted-sequencing with degenerate primers of three nuclear genes: heat shock protein90 (HSP90), elongation factor 1 alpha (EF1α) and beta tubulin (βtub). BLAST searches of ITS sequences of isolates of this study (accession nos. OP180065, OP180066) in NCBI GenBank showed 98.5 to 99.6% identity with the ITS sequence of P. gonapodyides (accession nos. MN513238.1, MG753496.1). Multiplex targeted sequencing also identified both isolates as a P. gonapodyides (accession nos. SRR20227809, SRR20227807) when mapped with the reference sequences (accession nos. HSP90: KX251233.1, EF1α: KX251231.1, β-tub: KX639710.1). Pathogenicity was confirmed by inoculating mycelial suspension of one isolate of P. gonapodyides on root of intact plants and mycelial plugs of two isolates on detached stems of the raspberry plants, 'Chemainus' in the greenhouse using methods described in Sapkota et al. 2022. Two experiments were conducted with three replicates in each test. Experiments were arranged using completely randomized design. In detached stem assays, distinct dark-lesion symptom appeared at 7 to 9 days after inoculation while uninoculated control stems remained asymptomatic. Intact plants showed wilting and foliar symptoms 15 days after inoculation and progressed higher at 4 to 5 weeks after inoculation. Root infection with dark brown to black color was observed when roots were assessed at 5 weeks after inoculation. The diseased root and crown tissues tested positive for Phytophthora in Agdia ImmunoStrip and P. gonapodyides was re-isolated and confirmed with multiplex-targeted sequencing. Phytophthora gonapodyides was previously reported from raspberry in Chile (Wilcox and Latorre 2002). To our best knowledge, this is the first report of P. gonapodyides infecting red raspberry in British Columbia, Canada. The detection of new Phytophthora species on raspberry may become a new potential problem to growers in addition to P. rubi, which is already a major cause of raspberry decline in the region